The Role of Extra Virgin Olive Oil in Suppressing Oxidative Stress through Reducing Superoxide Dismutase Activity in Ratus Novergicus Preeclampsia Model - Dwi Norma Retnaningrum; Wenny Rahmawati (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2026)
Oxidative stress is a key factor in the pathophysiology of preeclampsia. Preeclampsia is characterized by hypertension and proteinuria. Superoxide Dismutase (SOD) will decrease when reactive oxygen species (ROS) are overproduced. Extra Virgin Olive Oil (EVOO) contains polyphenols and vitamin E, which are known to have strong antioxidant properties. The aim of this study was to assess how EVOO supplementation affects SOD activity in a rat model of preeclampsia (Rattus norvegicus). Pregnant rats were divided into a normal control group, a preeclamptic control group administered with L-NAME, and treatment groups receiving L-NAME and different doses of EVOO in a post-test control group design. Spectrophotometry was used to measure SOD activity. The results showed a significant difference between the SOD activity of the control and treatment groups (P value = 0.002). The optimal EVOO dose returned SOD activity to near normal control levels. In conclusion, EVOO supplementation shows potential as an adjunct therapy to reduce oxidative stress in preeclampsia by increasing SOD activity.